Uso de materiais diretos e indiretos para amplas restaurações: implicações clínicas e laboratoriais - Skupien, Jovito Adiel (2014)
Glass fiber posts and composite resins are widely used materials in restorative dentistry. The various forms of presentation and technical approach, as well as different handling prior to their use, can result in diverse outcomes, which can determine the success or failure of the restorative procedure. Thus, the aim of this study was to evaluate the performance of glass fiber posts and composite resins in front of several factors related to it uses in dentistry. For this, the study was divided into three parts: An in vitro study, an in vivo study and a systematic review. The in vitro study aimed to evaluate the effect of cementation delay of indirect composite resin restorations in previously hybridized dentin. Three strategies of cementation were tested through different protocols. Beam-shaped specimens from tooth/restoration were obtained and submitted to microtensile testing to evaluate the bond strength and types of failures, where the results were analyzed by ANOVA and Tukey s post hoc tests and linear regression. Regular cement and adhesive threestep etch-and-rinse adhesive system showed the highest values of bond strength, followed by the same cement and two-step etch-and-rinse adhesive system and the lowest values for self-adhesive cement groups. Linear regression showed an improvement in the bond strength values when three-step adhesive system was used, however, all groups had adequate values of bond strength, even in unfavorable situations. The randomized clinical trial evaluated the longevity of metal-ceramic crown and composite resin restorations performed in endodontically treated teeth that received a glass fiber post. Fifty-six severely damaged teeth but with at least one entire wall were randomly allocated into two groups according to the type of restoration. The longevity was assessed through Kaplan-meier and clinical evaluation by descriptive analysis. The recall rate was 100%, fifty-six teeth were re-evaluated with no absolute failure. However, eight composite resin restorations had failed (all reparable). A significant difference between type of restoration was found. Indirect restorations provided higher acceptable clinical performance after two-year of followup, although composite failures were liable to repair. The systematic review compared factorts that can influence retention of glass fiber posts to intraradicular based on in vitro studies which compared the bond strength of resin cements. Searches were carried out in Pubmed and Scopus database up to December 2013. Thirty-four studies were included in the review and several variables were extracted. The presence of endodontic treatment significantly decrease the bond strength, meanwhile other variables can influence according to the type of resin cement. Thus, factors as type of cement application and pretreatment of post can influence glass fiber post retention, however, self-adhesive resin cements are less sensitive to luting procedures